Who knows what Mary knew? An experimental study. (19th May 2022) - Gregory, Daniel; Hendrickx, Malte; Turner, Cameron
ABSTRACT: This paper reports the results of an experimental philosophy study of intuitions among members of the general US population regarding a version of Frank Jackson's famous 'Mary in the black and white room' thought experiment. A large majority of respondents (82.1%, significantly above chance) reported having the intuition which is critical to the thought experiment, i.e., that Mary does not know what it is like to see red before she actually sees red. The intuition was pervasive across demographic groups.